Hubungan Lemak Viseral dan Massa Otot dengan Kadar Glukosa Darah Sewaktu Pasien Diabetes Mellitus Tipe 2 - Desti Ambar Wati; Nuzila Meysa Rhasetia (JURNAL RISET GIZI, 2025)
Background: Visceral fat and skeletal muscle mass are important components in glucose metabolism regulation, particularly in patients with type 2 diabetes mellitus (T2DM). Visceral fat is aasociated with insulin resistance, while skeletal muscle serves as the primary site of glucose uptake after meals. Objective: To analyze the association between visceral fat and muscle mass with random blood glucose levels in patients with T2DM. Methods: This cross-sectional study was conducted in July 2024 at the Kota Agung Primary Health Center, Tanggamus Regency, involving 58 T2DM patients selected through purposive sampling. Visceral fat and muscle mass were measured using bioelectrical impedance analysis (BIA), and random blood glucose levels were assessed using a glucometer. Data were analyzed using Pearson’s correlation test. Result: A significant positive association was observed between visceral fat and random blood glucose levels (r = 0.387, p = 0.003). Conversely, a significant negative association was found between muscle mass and random blood glucose levels (r = –0.386, p = 0.003). Female patients generally showed higher visceral fat, lower muscle mass, and higher random blood glucose levels than male patients. Conclusion: Visceral fat is positively associated, and skeletal muscle mass is negatively associated with random blood glucose levels in T2DM patients. These findings highlight the importance of body composition in glycemic control and suggest that interventions targeting visceral fat reduction and muscle mass preservation may be effective in managing T2DM.